Sublethal Effects of Diesel on Total Protein Levels and Cholesterol in Tympanotonus Fuscatus - OS Edori; IB Nwoke; ES Edori (Journal of Applied Sciences and Environmental Management)
Periwinkles (Tympanotonus fuscatus) of variable sizes between 4.5 to 5.5cm were handpicked at the Eagle Cement area of the New Calabar River and subjected to different levels of diesel contamination (0.00, 250.00, 300.00, 350.00, 400.00 and 450.00ml/L) for six days in a renewal assay to examine its effect on two metabolites (total protein content and cholesterol levels). Total protein content and cholesterol levels were examined in the muscle and viscera tissues of the periwinkles. Statistical analysis showed significant (P>0.05) variation in total protein content and cholesterol levels in the  tissues. Total protein content were significantly (P>0.05) lower in value in the treatment groups when compared to the control in both the muscle and the viscera of the periwinkle. While cholesterol levels were significantly (P>0.05) lower or higher in value than that of the control. This study showed that exposure of periwinkles (Tympanotonus fuscatus) to diesel toxicity could cause deleterious effects or changes in the organism biochemistry.